Summaries of SpS17 Discussions IAU GA 2012 Special Session on Light Pollution. (5th March 2015) - Walker, Constance E.; Parks, Bob; McKenna, Dan; Sefako, Ramotholo; Smith, Malcolm; Galadí-Enríquez, David
Abstract : To address light pollution issues, IAU Commissions 41, 46, 50, and 55 are involved in getting the word out to the public and IAU members via cultural, educational, technical; however, efforts can always improve and evolve. To carry out a successful light pollution abatement program supported by the IAU, it takes a diversity of groups, professions, and disciplines with their collective knowledge and experience. In manifesting dark skies awareness effectively, we are stronger together than we are alone; therefore, combining efforts of Commissions 41, 46, 50 and 55 with organizations like the International Dark-Sky Association, Astronomers Without Borders, The World at Night and partnering with events like Earth Hour or GLOBE at Night is a good step forward.